2021
DOI: 10.1177/00332941211028998
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders, Risky Behaviors, and Adversity: The Moderating Role of Resilience

Abstract: Individuals with personality disorders (PDs) comprise 30% to 40% of individuals receiving mental health treatment. Treatment of PDs is exceedingly difficult; therefore, research has focused on PD etiology and preventative factors. One known influence on PD etiology is adverse childhood experiences (ACEs). ACEs are associated with increased prevalence of several health risk behaviors (HRBs), including engagement in substance use, criminal, and risky sexual behavior. One protective factor, childhood resiliency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 84 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…Our eight-week intervention study revealed that meditation significantly increased parents’ resilience while reducing parental burnout. Flynn et al (2021) found that individuals with higher levels of resilience exhibited faster physiological and emotional recovery from negative consequences; parental burnout can be seen as a negative consequence parents face. Previous studies showed that meditation effectively benefitted self-control and development ( Brown and Ryan, 2003 ; Kiken and Shook, 2012 ), which can help parents better cope with parenting stress during the pandemic ( Behan, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our eight-week intervention study revealed that meditation significantly increased parents’ resilience while reducing parental burnout. Flynn et al (2021) found that individuals with higher levels of resilience exhibited faster physiological and emotional recovery from negative consequences; parental burnout can be seen as a negative consequence parents face. Previous studies showed that meditation effectively benefitted self-control and development ( Brown and Ryan, 2003 ; Kiken and Shook, 2012 ), which can help parents better cope with parenting stress during the pandemic ( Behan, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study involving 111 individuals who had breached the law reported notably low levels of resilience among the participants (Nowakowski and Wróbel 2021). Research suggests that adverse childhood experiences can impact resilience, potentially leading to behavioral issues and personality disorders in adulthood (Flynn et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Antisocial personality disorder (ASPD) is a mental disorder characterized by problems such as adherence to social rules, criminal tendencies, neglection of individual or social consequences of crimes, deception of others for personal gain, and emotional weakness (Fisher andHany 2019, APA 2013a). In 2013, the condition was included in the Alternative Model for Personality Disorders "Areas that Require Further Research" in the Diagnostic and 421 Psikiyatride Güncel Yaklaşımlar-Current Approaches in Psychiatry Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) by the American Psychiatric Associatio (APA 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…It must be mentioned that researchers who considered resilience as a personality trait equated the term resiliency with resilience, but the dominant view in the literature is that the two terms should be considered separately because it has been found that resilience cannot be a personality trait because resources in the environment can play an even greater role in coping with adversity than individual resources (Liebenberg VanderPlaat and Dolan, 2020). Resiliency is positively associated with life satisfaction (Beutel, Glaesmer, Decker, Fischbeck and Brähler, 2009;Lau, Feher, Wilson, Babcock and Saklofske, 2018) and has been shown to reduce the negative effects associated with ACE by strengthening the mechanisms of coping with stress, emotional intelligence, and overall functioning (Flynn, Parnes and Conner, 2021).…”
Section: Introductionmentioning
confidence: 99%